Analisis Strategi Pendidikan Karakter Melalui Hukuman Preventif - Ma`arif, Muhammad Anas (Taallum: Jurnal Pendidikan Islam, 2018)
The importance of character education for all levels raises various strategies in applying it. Punishment is one of strategies which was rarely used in the study of character education, therefore, the writer attracted to examine it. This study aimed to explain the character education strategies through punishment. This research used library research by collecting several related books and journals to analyze the content of the character education strategies through punishment. This study found that punishment was a preventive action of activities which did not match to the ethical values of character education. The punishment is the same as khauf and raja in the Sufi term. The character education strategy through punishment becomes one of disciplinary and habituation supports for learners in internalizing character education.